The relation between the depth of field and the visual fatigue caused by stereoscopic Wayang Kulit shadow images. (14th February 2019) - Hasanah, Nurul; Parikesit, Gea Oswah Fatah; Kusumaningtyas, Indraswari
Along with the development of visual technology, Wayang Kulit can be displayed stereoscopically using two light sources which are equipped by red and cyan filters, a flat screen, the puppet, and a pair of 3D glasses. While viewing the stereoscopic shadow image, the viewer's eyes will converge at a point to get a single image and the lenses accommodate to get a clear image. The position of the stereoscopic shadow image which is not located on the screen may lead to visual fatigue. By performing the mathematical analysis using geometrical optics, it can be concluded that both the depth of field range and the position of the stereoscopic shadow image depend on the position of the viewer relative to the screen. In order to avoid the visual fatigue, the viewers should carefully choose the position, which is far enough to avoid the visual fatigue, but close enough to maintain the stereoscopic effect.